Fibroblast Growth Factor 15–Dependent and Bile Acid–Independent Promotion of Liver Regeneration in Mice. Issue 5 (8th October 2018) - Kong, Bo; Sun, Runbin; Huang, Mingxing; Chow, Monica D.; Zhong, Xiao‐Bo; Xie, Wen; Lee, Yi‐Horng; Guo, Grace L.
Abstract : The role of intestine‐derived factors in promoting liver regeneration after partial hepatectomy (PHx) are not entirely known, but bile acids (BAs) and fibroblast growth factor 15 (Fgf15) that is highly expressed in the mouse ileum could promote hepatocyte proliferation. Fgf15 strongly suppresses the synthesis of BAs, and emerging evidence indicates that Fgf15 is important for liver regeneration. The mechanisms by which Fgf15 promotes liver regeneration are unclear, but Fgf15 may do so indirectly by reducing BA levels and/or directly by promoting cell proliferation. However, it remains undetermined whether these two mechanisms are independent or integrated. In this study, we aimed to clarify these relationships by generating Fgf15 Tet‐Off, transgenic mice ( Fgf15 Tg) that had very low BA levels as a result from overexpressed Fgf15‐mediated suppression of BA synthesis. Compared with wild‐type mice, the Fgf15 Tg mice showed increased hepatocyte proliferation even without surgery, and a further induction of the genes in cell‐cycle progression after PHx. Moreover, overexpression of Fgf15 by adeno‐associated virus (AAV)‐ Fgf15 transduction or treatment with the recombinant Fgf15 protein led to increased cell proliferation in vivo . Furthermore, Fgf15 Tg mice exhibited an earlier and greater activation of mitogen‐activated protein kinase, signal transducer and activator of transcription 3, and NF‐κB signaling pathways in the priming stage, and a disruption of the hippo signaling pathway in the termination stage of liver regeneration. Conclusion: Direct in vivo evidence demonstrates that Fgf15 is critical in stimulating the phases of priming and termination of liver regeneration that are critical for cell survival and liver‐size determination, independent of BA levels. (Hepatology 2018; 00:000‐000).